Analisa Pengukuran Tingkat Kepuasan Pengguna Aplikasi Daytrans Dengan Kerangka Kerja Pieces Framework - Purba, Antonius; Sihotang, Jay Idoan (Universitas Muhammadiyah Magelang, 2023)
Daytrans is a company that is developing and operates in the field of land transportation services and sending goods between provinces. Based on the results of the author's observations, it was found that no analysis of Daytrans Bandung consumer satisfaction, especially Dipatiukur, had ever been carried out. The main objective of this research is to analyze and measure the level of satisfaction with system service quality. The PIECES method was used to analyze the data in this research. And the Slovin formula was used to determine the sample size of 100 respondents. This number is obtained from measuring the tolerable error limit of 10%. The final results of the questionnaire calculation using the Likert scale and variables in the PIECES Framework produced an average score of 4.47. So that in general service users feel satisfied with the Daytrans Application system services.